Mineralogical and Geochemical Studies of Bone Detritus of Pleistocene Mammals, Including the Earliest in Northern Eurasia Humans - V. I. Silaev; D. V. Ponomarev; S. M. Slepchenko; A. A. Bondarev; D. V. Kiselеva; I. V. Smoleva; A. F. Khazov (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2015)
Article presents the preliminary results of mineralogical and geochemical studies of the primary and epigenetic properties of the bio-mineral and protein components in the fossil bone detritus as an example of first step of continued interdisciplinary research program. During the further implementation of this program, it is expected not only to solve a set of interrelated mineralogical, paleontological, paleoecological, paleoclimatic, and archaeological problems, but also to obtain new knowledge about the coevolution of organic, organo-mineral and inorganic substances in the geological history. The main objects of study are the fossil remains of the large Pleistocene mammals (mammoths, woolly rhinoceroses, deer, elk, horses, bison, cave and brown bear) found on the territory of the Pechora Urals (62-67 ° N) , South Pri-Irtyshie in Western Siberia (57-58 ° N), and Northern Taymyr (75-77 ° N). The oldest bone of Homo sapiens (Ust-Ishim human) found in Northern Eurasia and remains of medieval Tobol and Irtysh Turk will be investigated as well. The results of previous studies of skin and hair of biological material from today's wild fisheries (analogues Pleistocene mammals), wild and domestic animals are considered as the reliable prerequisites for planned isotopic and geochemical studies. Use of cutting-edge research techniques will allow determining the chemical composition of bones; the elemental composition of bone collagen and bone proteins; the degree of crystallinity of bone bioapatite, and phase composition of xenomineral impurities; the isotopic composition of carbon, oxygen, and nitrogen in bioapatite and collagen; the actual molecular and crystal structure of the protein biomineral, and bone substance; the concentration of trace elements; the conditions and duration of burial and reburial of bone detritus; bone collagen bacterial degradation at an early stage of fossilization. It is expected that the implementation of the proposed project will contribute to significant advance in knowledge of the material history of the Earth's biosphere.